The Paradigm Shift of Ophthalmology in the COVID-19 Era - Campos A (Dove Medical Press, 2020)
António Campos,1– 3 Nuno Oliveira,1 Joana Martins,1 Henrique Arruda,1 João Sousa1,3,4 1Department of Ophthalmology, Centro Hospitalar de Leiria EPE, Leiria 2410-197, Portugal; 2Institute for Clinical and Biomedical Research (iCBR), Faculty of Medicine, University of Coimbra, Coimbra 3000-548, Portugal; 3ciTechCare, Center for Innovative Care and Health Technology, Polytechnic Institute of Leiria, Leiria 2411-901, Portugal; 4Medical Sciences Department, Faculty of Health Sciences, University of Beira Interior, Covilhã, PortugalCorrespondence: António CamposCentro Hospitalar de Leiria EPE, Rua de Santo André, Leiria 2410-197, PortugalTel +351 244 81700Email antonio.figueiredo@chleiria.min-saude.ptObjective: To describe how a fixed regimen of intravitreal injections (IVI) was helpful to continue activity during the COVID-19 outbreak and lockdown and to address basic conditions to resume activity.Methods: A fixed regimen of IVI was conceived to significantly reduce the number of visits while keeping a number of injections related to the best outcomes. We retrospectively collected data of surgeries performed in 2019 and in the first seven months of 2020 and from OCTs in the first semester of 2020.Results: IVI per month, from January to July 2020, were 304, 291, 256, 204, 276, 297 and 322, respectively. Phacoemulsification surgeries in the same period were 397, 408, 171, 0, 304, 391 and 389. Posterior vitrectomies were 23, 21, 17, 10, 21, 28 and 25. Laser sessions were 44, 26, 33, 17, 23 and 33, respectively. OCTs dropped from a mean of 25.7 per day in the first half of March 2020 to 5.8 per day in the second half of March. A mean of 6.5 OCTs per day was made in April, rising to 19.1 in May and 39.5 in June.Conclusion: It was possible to keep the ophthalmological activity during the pandemic outbreak due to the existence of a pre-scheduled fixed regimen for IVI and to the availability of personal protective equipment. The air-borne nature of the peril we are facing addresses the need to evaluate the physical conditions of health facilities, including ventilation, size of waiting and consult rooms and the need to avoid elevators.Keywords: COVID-19, SARS-CoV-2, fixed regimen, intra-vitreal injections, resume activity, RT-PCR testing